The effect of gauge length on axially incident P-waves measured using fibre optic distributed vibration sensing - Dean, Tim; Cuny, T.; Hartog, A. (Wiley-Blackwell, 2017)
Â© 2016 European Association of Geoscientists & Engineers Distributed vibration sensing, also known as distributed acoustic sensing, is a relatively new method for recording vertical seismic profile data using a fibre optic cable as the sensor. The signal obtained from such systems is a distributed measurement over a length of fibre referred to as the gauge length. In this paper, we show that gauge length selection is one of the most important acquisition parameters for a distributed vibration sensing survey. If the gauge length is too small, then the signal-to-noise ratio will be poor. If the gauge length is too large, resolution will be reduced and the shape of the wavelet will be distorted. The optimum gauge length, as derived here, is a function of the velocity and frequencies of the seismic waves being measured. If these attributes vary considerably over the depth of a survey, then the use of different gauge lengths is recommended. The significant increases in data quality resulting from the use of multiple gauge length values are demonstrated using field data.